Sedative Effect of Lemongrass (Cymbopogon nardus) Aromatherapy through Inhalation Route on Mice (Mus musculus) Behavior - Surachmat, Hilmy Luqman; Arianto, Eko Fuji; Khairani, Shafia (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
Aromatherapy is an alternative practice in natural medicine that uses essential oil derived from various plants. Essential oil is found in over 17,000 plant species, including lemongrass (Cymbopogon nardus). Lemongrass essential oil contains several active components with potential sedative effects, such as linalool. Therefore, this study aimed to evaluate the potential sedative effect of lemongrass essential oil aromatherapy through inhalation route as an alternative preparation. Mice (Mus musculus) were divided into 5 groups, namely negative and positive control (Diazepam 0.012 mg/kg), as well as treatment 1 (P1, 30-minute exposure), 2 (P2, 60-minute exposure), and 3 (P3, 90-minute exposure). Essential oil of lemongrass was extracted using the distillation method, followed by phytochemical testing. Behavioral observations were carried out using Chimney test method. The results of Chimney test showed that lemongrass aromatherapy had no sedative effect. This result was evident by the insignificant differences (P > 0.05) between negative control groups and both P1 and P3, as well as P1 and P3. Furthermore, P2 showed a potential stimulant effect based on Chimney test results.